Biomass retrofit for existing solar organic Rankine cycle power plants: Conceptual hybridization strategy and techno-economic assessment. (15th September 2019) - Oyekale, Joseph; Heberle, Florian; Petrollese, Mario; Brüggemann, Dieter; Cau, Giorgio
Highlights: Biomass retrofit for existing solar ORC plants can improve efficiency and flexibility. Retrofit can increase working hours and economic competitiveness of solar ORC plants. Relative deviation of implemented ORC off-design models from real plant data is 3%. The proposed hybridization strategies can be extended to new plant designs. The benefits of implemented hybrid solar-biomass schemes are higher for new designs. Abstract: This study aims to investigate techno-economic benefits of biomass retrofit for practical concentrated solar power (CSP) organic Rankine cycle (ORC) power plants. In this regard, technical parameters of an existing CSP-ORC plant currently running in Ottana (Italy) have been adopted for analyses. The plant consists of linear Fresnel collectors solar field, coupled with a two-tank oil-based thermal energy storage (TES) device, feeding a 630 kWe ORC plant. Fixed and modular biomass hybridization approaches were proposed for retrofit. In the fixed approach, biomass furnace constantly supplies thermal energy to ORC such that a pre-determined minimum power production is guaranteed, with or without solar thermal energy availability. In the modular approach, biomass furnace is regulated to supply balance thermal energy needed to continuously operate the ORC at its full capacity. Furthermore, beyond the biomass retrofit case study, a newly integrated design case study was introduced, with modified solar field and TES capacity. By using the meteorological conditions of Ottana, results of techno-economic performance for the retrofit case study showed that annual net electrical efficiency increases by 4–5 percent points, relative to the solar-only ORC plant. Marginal levelized cost of electricity (LCOE) of between 103 €/MWh and 109 €/MWh were obtained. Also, marginal net present value (NPV) ranges from 1.83 M€ to 3.22 M€. For the newly integrated design case study, results showed that design case with modular hybridization approach represents the highest annual net electrical efficiency, at 19.8%. For this approach, economic results showed that LCOE ranges between 130 €/MWh and 146 €/MWh. Beyond current state-of-the-art, the results obtained in this study show that biomass retrofit for existing CSP-ORC plants can lead to higher full-load operation hours and more prospective plant economics. Moreover, the implemented modular approach enables scheduled power profile to be followed, thereby enhancing plant dispatchability.